2021
DOI: 10.33549/physiolres.934701
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Three Adipocytokines (Adiponectin, Resistin and Visfatin) And Thyroid Status in Patients With Type 2 Diabetes Mellitus and Autoimmune Thyroiditis

Abstract: Autoimmune thyroiditis (AIT) and type 2 diabetes mellitus (DM2) are the most common endocrinological diseases worldwide. Relation between these diseases explains several hypotheses. One of them is influence of some adipocytokines. This study evaluated association between three adipocytokines (adiponectin, resistin and visfatin) and thyroid and glycid status in patients with DM2 and AIT compared to the control group (CG). The group consisted of four subgroups: patients with DM2 without thyreopathies, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This showed that mycosubtilin had the same effect as that of n-butanol site metabolites, suggesting that mycosubtilin could reduce body weight gain in mice by reducing fat accumulation. As a white fat, epididymal fat can not only store energy in the form of TG but can also act as an endocrine organ, secreting a variety of adipocytic factors, such as lipocalin and tumor necrosis factor et al (Sotak et al, 2021). The mice's liver and blood tests revealed that the n-butanol sites and mycosubtilin could significantly reduce the TG and LDL concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that mycosubtilin had the same effect as that of n-butanol site metabolites, suggesting that mycosubtilin could reduce body weight gain in mice by reducing fat accumulation. As a white fat, epididymal fat can not only store energy in the form of TG but can also act as an endocrine organ, secreting a variety of adipocytic factors, such as lipocalin and tumor necrosis factor et al (Sotak et al, 2021). The mice's liver and blood tests revealed that the n-butanol sites and mycosubtilin could significantly reduce the TG and LDL concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that mycosubtilin had the same effect as that of n-butanol site metabolites, suggesting that mycosubtilin could reduce body weight gain in mice by reducing fat accumulation. As a white fat, epididymal fat can not only store energy in the form of TG but can also act as an endocrine organ, secreting a variety of adipocytic factors, such as lipocalin and tumor necrosis factor et al [35]. The mice's liver and blood tests revealed that the n-butanol sites and mycosubtilin could signi cantly reduce the TG and LDL contents.…”
Section: Discussionmentioning
confidence: 99%